THE INFLUENCE OF SAMPLING TIME TO SERUM GLIAL FIBRILLARY ACIDIC PROTEIN (GFAP) LEVELS IN ACUTE STROKE - Raisa, Neila; Sujuti, Hidayat; Rahayu, Masruroh; Dalhar, Mochamad; Purnomo, Hari (Malang Neurology Journal, 2019)
Background: Serum Glial Fibrillary Acidic Protein (GFAP) is a great potential for biomarker that is widely studied as a diagnostic biomarker of acute stroke. Sampling within 6 hours after onset is the best time window, but in Indonesia, stroke patients often arrive late more than 6 hours.Objective: To identify the difference in time of blood sampling with serum GFAP levels within 24 hours onset of ischemic stroke (IS) patients and intracerebral hemorrhage (ICH) strokes.Methods: Cross-sectional analysis with purposive sampling, sampling in IS and ICH strokes that arrive at the ER within 24-hour on-site. The serum GFAP examination was performed with ELISA.Results: In this study, 41 acute stroke patients with 24-hour onset of each stroke were grouped into group 1 (<6 hours), group 2 (6-12 hours) and group 3 (12-24 hours). One Way ANOVA and Tukey's analysis showed no significant difference in GFAP levels among the three groups in both IS and ICH. Conclusion: There was no significant difference in GFAP levels in samples <6 hours, 6-12 hours, and 12-24 hours in ischemic strokes and ICH strokes.